2018
DOI: 10.1108/hff-04-2017-0149
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MHD mixed convection with non-uniform heat source/sink and cross-diffusion over exponentially stretching sheet

Abstract: Purpose The purpose of this paper is to investigate the magnetohydrodynamics mixed convection flow over an exponentially stretching surface in the presence of non-uniform heat source/sink and cross-diffusion. Adequate non-similar transformations are used to transform governing mixed convection boundary layer equations to dimensionless form. Design/methodology/approach These dimensionless partial differential equations are solved by using implicit finite difference scheme in conjunction with Quasi-linearizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Various researchers have studied the importance of heat generation/absorption and variable thermal conductivity for the purpose of heat transfer analysis. Patil et al [15] contemplated the fluid above an exponentially stretching surface along with MHD and nonuniform heat source/sink. ey found that temperature profile diminishes by escalating the thermal relaxation effect.…”
Section: Introductionmentioning
confidence: 99%
“…Various researchers have studied the importance of heat generation/absorption and variable thermal conductivity for the purpose of heat transfer analysis. Patil et al [15] contemplated the fluid above an exponentially stretching surface along with MHD and nonuniform heat source/sink. ey found that temperature profile diminishes by escalating the thermal relaxation effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, as Prandtl and Deborah’s numbers increased, the temperature species decreased. While Patil et al (2018) studied MHD-mixed convection flow across an exponentially stretched area with a nonuniform sink/heat source and cross-diffusion. The results reveal that, as the magnetic effect is reduced, the velocity profile improves.…”
Section: Effects Of Various Parameters Of Mass and Heat Transfer Rate...mentioning
confidence: 99%
“…Patil et al [ [67] , [68] , [69] , [70] , [71] ] examined the behavior of a non-Newtonian fluid model under convective boundary situations and evaluated it numerically by employing the finite difference quasilinearization method. Additionally, Patil et al [ [72] , [73] , [74] , [75] , [76] ] looked at the mass and heat transfer of various geometries and diverse nanoparticle types.…”
Section: Introductionmentioning
confidence: 99%